Verrucous Carcinoma of the Larynx Presenting as a Hairy Whitish Tumor. Issue 4 (1997) - Kawaida, Masahiro; Fukuda, Hiroyuki; Kohno, Naoyuki
Abstract : A patient was encountered with verrucous carcinoma of the larynx that presented as a hairy whitish tumor. There was a recurrence because simple excision with forceps by endolaryngeal microsurgery was performed in the first operation. However, in the second operation endolaryngeal microscopic laser surgery using a direct laryngoscope was performed and followed by adjuvant chemotherapy with oral UFT, a combination of uracil and tegafur in a molar ratio of 4:1. The patient's course has been favorable to date. The case is reported in this paper and discussed from the viewpoint of diagnosis and treatment of this neoplasm.